1993
DOI: 10.1111/j.1745-493x.1993.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing Perf ormance Evaluation: An Investigation of Diff erent Perspectives

Abstract: Purchasing professionals play essential roles in the purchasing decision‐making process, coordinating and guiding all buying team members to achieve the best performance of the group as a whole. This research project examines ten key purchasing performance measures as viewed by three types of players in the purchasing decision‐making processnamely, purchasing mangers, buyers, and internai customers. A key finding of the study is that the quality of purchased items presently is viewed as the most important meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 2 publications
0
36
0
Order By: Relevance
“…_Operational purchasing performance is captured in terms of cost, quality, delivery and flexibility performance, whereas innovation represents strategic dimension of purchasing performance. The measures underlying these dimensions include cost and quality of inputs/outputs, cost of purchasing activities, procurement cycle times, on-time deliveries, inventory turns, percentage of JIT suppliers, ability to respond quickly to design changes, the ability to respond quickly to changes in production volumes or schedules, and access to new technologies, and involvement in new product development (Chao, Scheuing, and Ruch 1993;Krause, Pagell, and Curkovic 2001;Leenders et al 2002).…”
Section: Purchasing Performancementioning
confidence: 98%
“…_Operational purchasing performance is captured in terms of cost, quality, delivery and flexibility performance, whereas innovation represents strategic dimension of purchasing performance. The measures underlying these dimensions include cost and quality of inputs/outputs, cost of purchasing activities, procurement cycle times, on-time deliveries, inventory turns, percentage of JIT suppliers, ability to respond quickly to design changes, the ability to respond quickly to changes in production volumes or schedules, and access to new technologies, and involvement in new product development (Chao, Scheuing, and Ruch 1993;Krause, Pagell, and Curkovic 2001;Leenders et al 2002).…”
Section: Purchasing Performancementioning
confidence: 98%
“…Technical Chao et al [1993] Quality, delivery speed, reliability, price Wei, et al [1997] Supplier's supply history, product price, technical ability and transportation cost Krause et al [2001] Quality, delivery, flexibility, cost, innovation by the supplier is essential for the manufacturer's attempt to gain competitive advantage. Empirical articles try to find out the most important criteria for purchasing managers when selecting suppliers.…”
Section: Focusesmentioning
confidence: 99%
“…The key to enhancing the quality of decision making in supplier selection include the powerful computer-related concepts, tools and techniques that have become available in recent years (Wei et al, 1997). Chao et al (1993) concluded that quality and on-time delivery are the most important attributes of purchasing performance. Ghodsypour & O'Brien (1998) agreed that cost, quality and service are the three main factors that should influence supplier selection.…”
Section: Outsourcing Decision Criteriamentioning
confidence: 99%